KENDALI SUPLAI NUTRISI DAN CAHAYA PADA HIDROPONIK TANAMAN SAWI PAKCOY DENGAN SISTEM NFT - Bagus Hadi Saputra (LPPM Poltek ST Paul, 2021)
Hydroponics is a technique of growing crops on a large scale without using a large area of land and is suitable for application in areas with limited land. The limitation of the hydroponic system is that it requires a controlled environment, especially for monitoring the degree of acidity of the water, the concentration of water nutrients to avoid plant quality and the need to control the light received by plants to carry out photosynthesis. This research is in the form of experimental research to control the supply of nutrients and lighting of mustard greens in hydroponics with the NFT system (nutrient film technique), whose working concept is to drain water to the mustard roots of pakcoy with a small flow. The results showed that the pH value is stable in the range 5.5-7 and when the light intensity is less than 3000 Lux, the LED light will light up. During planting to harvest the average pH sensor error is 4.88%, the TDS sensor is 3.99% and the BH1750 sensor is 6.78%. Yields with automation have a significant effect on the height, number and width of pakcoy mustard leaves with an average number of leaves 2.5 more and 0.86 wider than the nutrient supply system and manual lighting.